Six-year mortality in a street-recruited cohort of homeless youth in San Francisco, California - Auerswald, Colette L.; Lin, Jessica S.; Parriott, Andrea (PeerJ, 2016)
Objectives. The mortality rate of a street-recruited homeless youth cohort in the United States has not yet been reported. We examined the six-year mortality rate for a cohort of street youth recruited from San Francisco street venues in 2004. Methods. Using data collected from a longitudinal, venue-based sample of street youth 15–24 years of age, we calculated age, race, and gender-adjusted mortality rates. Results. Of a sample of 218 participants, 11 died from enrollment in 2004 to December 31, 2010. The majority of deaths were due to suicide and/or substance abuse. The death rate was 9.6 deaths per hundred thousand person-years. The age, race and gender-adjusted standardized mortality ratio was 10.6 (95% CI [5.3–18.9]). Gender specific SMRs were 16.1 (95% CI [3.3–47.1]) for females and 9.4 (95% CI [4.0–18.4]) for males. Conclusions. Street-recruited homeless youth in San Francisco experience a mortality rate in excess of ten times that of the state’s general youth population. Services and programs, particularly housing, mental health and substance abuse interventions, are urgently needed to prevent premature mortality in this vulnerable population.
Keywords: Homeless youth; Mortality; Longitudinal; Street sample; United states